Creation and Characterization of a Double Null Puroindoline Genotype in Spring Wheat. Issue 5 (15th July 2017) - Martin, John M.; Hogg, Andrew C.; Webster, Richard W.; Giroux, Michael J.
Abstract : Wheat ( Triticum aestivum L.) grain hardness is controlled by the Ha locus, which is composed of two closely linked genes, Puroindoline a ( Pina ) and Puroindoline b ( Pinb ). Hard grain results from mutations in either of the Pin genes. Previous results have shown that the Pina‐D1b ( Pina null) allele has harder grain than other naturally occurring Pin alleles. Our goal was to create, identify, and characterize a double null Pin genotype by identifying a Pinb null mutation in a variety carrying the Pina‐D1l null allele. Seeds of Fortuna, which has a premature stop codon in Pina, were treated with ethyl methanesulfonate. Two premature stop codon mutations were identified in Pinb using direct sequencing. The double null Pin haplotype was characterized after backcrossing to the parent variety Fortuna to create Pina null populations segregating for the presence of Pinb . The double null group was 6 units harder than the single null with no difference in other kernel characteristics. The milling characteristics differed between the two classes; the double null class had less break flour with a greater fraction of large and a smaller fraction of small flour particles compared with the single null class. Neither water absorption nor loaf volume was impacted by the change in grain hardness; however, Na2 CO3 tests indicated greater starch damage in the double nulls. The double null Pin genotype may find a niche in hard wheat products for which flours with larger particle size are desired.